Differences in the level of knowledge of young women before and after being given counseling about personal hygiene during menstruation at MTS Muhammadiyah Pulau Arbor in 2022 - Anggi Juliad Putri; Ningsih Saputri; Sukmawati (Journal of Midwifery and Nursing, 2023)
Personal hygiene during menstruation in young women is the behavior of young women in maintaining health and hygiene when experiencing menstruation, the cause of not doing Personal hygiene during menstruation is due to a lack of information and understanding which results in reproductive health problems such as pelvic inflammatory disease, reproductive tract infections and cancer cervix.This study aims to determine whether there are differences in the level of knowledge of young women before and after being given counseling about personal hygiene during menstruation. This study uses a comparative method with the design used is one group pretest-posttest design, meaning that research activities provide an initial test (pretest) before being given treatment, after being given treatment then give a final test (posttest). The research location was at MTs Muhammadiyah Pulau Punjung, Dharmasraya Regency. The total sampling research sample, the population in this study were all 19 class IX teenage girls. The data analysis used is univariate and bivariate analysis. Based on the results of research using Wiljoxon it was found that the P-Value = 0.000 <0. 05 means that there are differences in the level of knowledge of young women before and after being given counseling about personal hygiene during menstruation. The conclusion of this study is that there are differences in the level of knowledge of young women before and after being given counseling about personal hygiene during menstruation.